2021
DOI: 10.1002/aqc.3545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental variables on the number of births at California sea lion (Zalophus californianus) rookeries throughout the Gulf of California, Mexico

Abstract: 1. The 13 California sea lion breeding colonies in the Gulf of California (GoC), Mexico are each characterized by different population growth trends, including a variable number of births. Despite being located in a highly productive marine area, both the species' population and the number of births have declined significantly over the past few decades.2. The goal of this study was to assess the effects of certain environmental variables on the number of births at colonies in three regions (northern, central a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Proxies for marine productivity and biomass such as SST and landings of demersal fishes were found to have a strong influence on the number of agonistic interactions between SASL and SAFS. SST drives the mixing regimes of the Pacific Ocean and with those, significant changes in the concentrations and distribution of nutrients and plankton, the base component of oceanic food webs ( Laidre et al 2008 ; Doney et al 2012 ; Pelayo-González et al 2021 ). Therefore, there are significant correlations between the thermal regime of the ocean and the distribution of plankton determined through measurement of chlorophyll concentrations by satellites ( Bouffard et al 2018 ; Hao et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proxies for marine productivity and biomass such as SST and landings of demersal fishes were found to have a strong influence on the number of agonistic interactions between SASL and SAFS. SST drives the mixing regimes of the Pacific Ocean and with those, significant changes in the concentrations and distribution of nutrients and plankton, the base component of oceanic food webs ( Laidre et al 2008 ; Doney et al 2012 ; Pelayo-González et al 2021 ). Therefore, there are significant correlations between the thermal regime of the ocean and the distribution of plankton determined through measurement of chlorophyll concentrations by satellites ( Bouffard et al 2018 ; Hao et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sampling locations (numbered): 1, Isla Lobos; 2, San Esteban; 3, Isla Granito; 4, Los Cantiles; 5, El Rasito; 6, Los Machos; 7, Cabo San Lázaro; 8, Isla Santa Margarita. Modified from Pelayo-González et al (2021a). Illustration courtesy of Gustavo De La Cruz-Agüero.…”
Section: Methodsmentioning
confidence: 99%
“…Differences in life history traits and environmental conditions exist between California sea lions from the Pacific coast of the Baja California peninsula and those from the Gulf of California off of the coast of mainland Mexico (Szteren and Aurioles-Gamboa 2011; López-Arvide 2014; Rosas-Hernández et al 2018; Pelayo-González et al 2021a, 2021b; Hernández-Camacho et al 2021), and geographic isolation between populations may be accelerating their genetic divergence (González-Suárez et al 2009). Previous genetic studies indicated that California sea lions are separated into 5 subpopulations (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations